Roboticky asistované cévní rekonstrukce aorto-ilické oblasti - Dvorák, M; Novotný, T; Staffa, R (Rozhledy v chirurgii, 2011)
OBJECTIVES: The objective of the study was to evaluate the results of the robot-assisted laparoscopic aortoiliofemoral reconstructions in a group of 45 patients. MATERIALS AND METHODS: The procedure is performed using three surgical techniques--conventional for the dissection of the vessels in the groin and distal anastomosis creation; laparoscopic for the dissection of the abdominal aorta and robotic for the proximal anastomosis creation. Between May 2006 and May 2010 we operated on 45 patients (37 males, 8 females) at a mean age of 57 years for aortoiliac occlusive disease using robot-assisted laparoscopic approach. We assessed the perioperative and hospitalization data. RESULTS: We created 21 aortobifemoral, 22 aortofemoral and 2 iliofemoral bypasses. The median time of the proximal anastomosis creation was 23 minutes (range 18 to 50 minutes), median clamping time was 60 minutes (range 40 to 95 minutes), median total operating time was 295 minutes (range 180 to 475 minutes). The median estimated blood loss was 265 ml (range 50 to 1200 ml). The median ICU stay was 2 days (range 1 to 8 days). During the follow-up period (median 19 months; range 2 to 50 months), we observed 3 early occlusions (6.7%)--all due to an insufficient outflow. All occlusions were resolved by the extension of reconstructions. No renal, cardiac or pulmonary complications were observed. The 30-day mortality was 0%. Late complications: port-site hernia (2.2%). The secondary patency was 100%. CONCLUSIONS: The da Vinci robotic system allows a precise vascular anastomosis creation and blood loss minimization. The achieved results (clamping time, anastomosis time) are fully comparable to conventional vascular surgery. The robotic system eliminates the technical limitations of laparoscopic aortic anastomosis creation. Robot-assisted laparoscopic aortoiliofemoral bypass grafting seems a safe method with a low complication rate.
Keywords: Robotics; Vascular Surgical Procedures; arteria iliaca; Iliac Artery; Male; Humans; lidé; výkony cévní chirurgie; mužské pohlaví; ženské pohlaví; Female; lidé středního věku; robotika; aorta abdominalis; Aorta, Abdominal; Middle Aged